Taxation of Wage Income for Economic Justice - Phelps, Edmund S. (Quarterly Journal of Economics, 1973)
I. "Maximin" justice, 332. — II. Just taxation in two earnings models, 337. — III. Concluding remarks, 350. — Appendix, 351.